Ratiometric Near-Infrared Fluorescent Probes Based on Hemicyanine Dyes Bearing Dithioacetal and Formal Residues for pH Detection in Mitochondria - Yunnan Yan; Yibin Zhang; Shuai Xia; Shulin Wan; Tara Vohs; Marina Tanasova; Rudy L. Luck; Haiying Liu (Molecules, 2021)
Ratiometric near-infrared fluorescent probes (AH+ and BH+) have been prepared for pH determination in mitochondria by attaching dithioacetal and formal residues onto a hemicyanine dye. The reactive formyl group on probe BH+ allows for retention inside mitochondria as it can react with a protein primary amine residue to form an imine under slightly basic pH 8.0. Probes AH+ and BH+ display ratiometric fluorescent responses to pH changes through the protonation and deprotonaton of a hydroxy group in hemicyanine dyes with experimentally determined pKa values of 6.85 and 6.49, respectively. Calculated pKa values from a variety of theoretical methods indicated that the SMDBONDI method of accounting for solvent and van der Waals radii plus including a water molecule located near the site of protonation produced the closest overall agreement with the experimental values at 7.33 and 6.14 for AH+ and BH+ respectively.